Carl Nielsens 5. symfoni: Dens tilblivelse og reception i 1920rne - Fjeldsøe, Michael; Bergsagel, John (Danish Yearbook of Musicology, 1997)
Carl Nielsen’s 5th Symphony, its origin and reception in the 1920s In connection with the critical revision of Carl Nielsen’s 5th Symphony a number of interesting things have turned up which cast light on the origins of the symphony and its reception in the 1920s. Some of this information will naturally be available to the reader in the critical commentary that will accompany the publication of the work as volume 5 in series II of the Carl Nielsen Edition, which it is expected will be issued in 1997 by Wilhelm Hansens Musikforlag, Copenhagen. However, the symphony’s position as one of the most significant of the period – also in European perspective – is sufficient justification for a more extended treatment as well, in which the circumstances of its composition and of the reception it received from the public at that time, both inside and outside of Denmark, can be examined. In addition a hitherto unnoticed but important source of information concerning the composer’s intentions as regards the performance of the drum solo and the conclusion of the 1st movement is discussed and the attention given to certain special features of the source material may, it is hoped, contribute to a better understanding of the work. This article is concerned with the work from its conception until the printing of the first edition in 1926 and the source material is treated with particular attention to the changes undertaken by the composer during the process of composition. Furthermore, the conditions which especially contribute to the modern character of the work, namely Carl Nielsen’s individual attitude to tonality in the symphony and the consciously radical way in which he sets the side-drum up against the rest of the orchestra in the first movement, are discussed. This aspect of the work is pursued also in connection with its reception, in that particular emphasis is laid on the discussion concerning the symphony’s modernity which followed upon the first performance and the very impressive series of performances that took place both at home and abroad in the years 1922-1927. Particular attention is accorded the performance at the ISCM festival in Frankfurt a.M. in 1927 and the following performance in Königsberg, which is discussed here for the first time.